Supplementing the Faculty to Assist and the Radical Sanation of a Marriage in Fieri: a Case Study of the Decree Issued by the Local Ordinary of the Diocese of Tui-Vigo on September 27, 1990 - Białobrzeski, Tomasz (Prawo Kanoniczne, 2023)
The form of marriage is regulated in the Code of Canon Law in canons 1108-1123. Compliance with this form is one of the conditions required for validity. The case presented concerns a marriage that was contracted on 18 August 1990, in the Spanish diocese of Tuy-Vigo. Due to the lack of delegation from an assisting priest, the marriage was not validly contracted. In the subsequent proceedings, by virtue of canons 1161-1165 of the Code of Canon Law, its radical sanation was carried out.